Efficacy and safety of hepcidin-based screen-and-treat approaches using two different doses versus a standard universal approach of iron supplementation in young children in rural Gambia: a double-blind randomised controlled trial. Issue 1 (December 2016) - Wegmüller, Rita; Bah, Amat; Kendall, Lindsay; Goheen, Morgan; Mulwa, Sarah; Cerami, Carla; Moretti, Diego; Prentice, Andrew
Abstract Background Iron deficiency prevalence rates frequently exceed 50 % in young children in low-income countries. The World Health Organization (WHO) recommended universal supplementation of young children where anaemia rates are >40 %. However, large randomized trials have revealed that provision of iron to young children caused serious adverse effects because iron powerfully promotes microbial growth. Hepcidin – the master regulator of iron metabolism that integrates signals of infection and iron deficiency – offers the possibility of new solutions to diagnose and combat global iron deficiency. We aim to evaluate a hepcidin-screening-based iron supplementation intervention using hepcidin cut-offs designed to indicate that an individual requires iron, is safe to receive it and will absorb it. Methods The study is a proof-of-concept, three-arm, double blind, randomised controlled, prospective, parallel-group non-inferiority trial. Children will be randomised to receive, for a duration of 12 weeks, one of three multiple micronutrient powders (MNP) containing: A) 12 mg iron daily; B) 12 mg or 0 mg iron daily based on a weekly hepcidin screening indicating if iron can be given for the next seven days or not; C) 6 mg or 0 mg iron daily based on a weekly hepcidin screening indicating if iron can be given for the next seven days or not. The inclusion criteria are age 6-23 months, haemoglobin (Hb) concentration between 7 and 11 g/dL, z-scores for Height-for-Age, Weight-for-Age and Weight-for-Height > -3 SD and free of malaria. Hb concentration at 12 weeks will be used to test whether the screen-and-treat approaches are non-inferior to universal supplementation. Safety will be assessed using caregiver reports of infections, in vitro bacterial andP. falciparum growth assays and by determining the changes in the gut microbiota during the study period. Discussion A screen-and-treat approach using hepcidin has the potential to make iron administration safer in areas with widespread infections. If this proof-of-concept study shows promising results the development of a point-of-care diagnostic test will be the next step. Trial registration ISRCTN07210906, 07/16/2014